PERAN KANTOR PENGAWASAN DAN PELAYANAN BEA CUKAI (KPPBC) TIPE MADYA PABEAN C TEMBILAHAN DALAM PEREDARAN ROKOK ILEGAL DI KECAMATAN RETEH - Vitha Armiza Purnama; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The circulation of various goods does continue to occur in Indonesia in various ways carried out by the perpetrators. Increasing the circulation of illegal cigarettes is one of the obstacles that can hinder national development. Referring to Law Number 39 of 2007 concerning Excise, it is stated that offering or selling plain cigarettes or cigarettes without excise is punishable by imprisonment of 1 to 5 years, and/or a fine of 2 to 10 times the excise value to be paid. Therefore, the role of Customs and Excise in monitoring the circulation of illegal cigarettes is urgently needed. The purpose of this study was to determine the role of KPPBC TMP C Tembilahan in monitoring the circulation of illegal cigarettes. This study uses qualitative methods with data collection techniques are interview and documentation techniques. This research uses Role Theory according to Ralph Linton. Role is a set of concepts related to what individuals in society can do as organizations. The research method used in this research is qualitative research. The type of research is descriptive qualitative research. The location of the research is in Reteh Subdistrict, Indragiri Hilir Regency and at the Customs and Excise Service Supervision Office (KPPBC) Type C Customs Intermediate Tembilahan. The results of the study explain that the role of KPPBC TMP C Tembilahan in the circulation of illegal cigarettes in 2019 has not been maximized. This is evidenced by the ineffectiveness of several policies such as socialization activities, land patrols and market operations. As well as the factors causing the smuggling of illegal cigarettes that have not been fully resolved. Keywords : KPPBC, Circulation, Illegal Cigarettes.